1997
DOI: 10.1080/01635589709514497
|View full text |Cite
|
Sign up to set email alerts
|

Variability in anticancer lignan levels in flaxseed

Abstract: Flaxseed and its major mammalian lignan precursor secoisolariciresinol diglycoside have been shown to be protective against chemically induced carcinogenesis in animal models. Although flaxseed is the richest source of mammalian lignan precursors, it is not known whether these levels vary with source. Thus the objective of this study was to determine how lignan levels in flaxseed are affected by variety, growing location, harvest year, and seeding time. Ten varieties of flaxseed (AC Linora, Andro, Flanders, Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 22 publications
2
51
1
Order By: Relevance
“…In addition, there are various analytical methods for determining food values ; hence, databases compiled from published values determined by different methodologies may contain inherent errors. It has also been shown that the amount of lignans in food can differ according to crop variety, location, year of harvest and processing (Thompson et al, 1997;Kuijsten et al, 2005). Dietary measurement error associated with FFQs (food frequency questionnaires) is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are various analytical methods for determining food values ; hence, databases compiled from published values determined by different methodologies may contain inherent errors. It has also been shown that the amount of lignans in food can differ according to crop variety, location, year of harvest and processing (Thompson et al, 1997;Kuijsten et al, 2005). Dietary measurement error associated with FFQs (food frequency questionnaires) is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…Good sources of lignans in the United States and Europe are pumpkin seed (20 mg/100 g), sunflower seed, cranberry, black tea, coffee, garlic, broccoli, brans, and peanuts (62). Green tea is a rich source of lignans and a popular beverage in many Asian countries (63).…”
Section: Dietary Sourcesmentioning
confidence: 99%
“…The major nutritional components of flaxseed include oil, viscous lignanrich fibres (mucilage), protein and minerals, which are analyzed by American Oil Chemists Society (AOCS). Flaxseed is the richest source of a -linolenic acid (18:3n-3), soluble and insoluble fibre, and mammalian lignan precursor secoisolariciresinol diglucoside (SDG) (1,2). Flaxseed has long history of use in India.…”
Section: Introductionmentioning
confidence: 99%